W. Carrillo (Spain) : inter-departmental correspondence (copy) - Bolton, W. J.
027-0031-001 W. J. BOLTON. INTERNATIONAL. SIR WALTER CITRINE. 20TH MARCH, 1940. W. CARRILLO (SPAIN). W. Carrillo writes that he thinks deputations and letters are useless and that a Press and public campaign should be organised for the workers' leaders in Spain who it is reported are being shot by Franco. Do you think the present time is opportune? 292/946/27/31